A Comprehensive Strategy to Pain Management for Cancer Patients in an Inpatient Rehabilitation Facility - Pugh, Terrence M.; Squarize, Fabiana; Kiser, Allison L. (Frontiers in Pain Research, 2021)
Cancer pain has been shown to have a significant negative impact on health-related quality of life (HRQoL) for people experiencing it. This is also true for patients admitted to inpatient rehabilitation facilities (IRFs). An interdisciplinary approach is often needed to fully address a person's pain to help them attain maximum functional independence and to ensure a safe discharge home. Improving a patient's performance status in an IRF may also be a crucial determinant in their ability to continue receiving treatment for their cancer. However, if a person is determined to no longer be a candidate for aggressive, disease modulating treatment, IRFs can also be utilized to help patients and family's transition to comfort directed care with palliative or hospice services. This article will discuss the interventions of the multidisciplinary inpatient rehabilitation team to address a person's pain.